1975
DOI: 10.1002/maco.19750260207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Toluidines and Acridine Derivatives on Corrosion of 63/37 Brass in Nitric Acid Solution

Abstract: Among the inhibitor studied – o‐, m‐and p‐toluidines, acridine, phenazine and xanthine ‐ o‐toluidine and acridine have turned out to be excellent inhibitors of the corrosion of brass in nitric acid. As to the toluidine series the inhibiting power of the ortho isomer is superior to that of the para isomer. On the base of the results obtained the following order of efficiency may be established ‐ o‐toluidine ‐ p‐toluidine ‐ m‐toluidine ‐ acridine ‐ xanthine ‐ phenazine. The efficiency is probably due to the elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The use of acridines as corrosion inhibitors dates back to 1975 when Patel and Patel [34] used the weight loss (WL) technique to examine the anticorrosion properties of acridine and analogous phenazine and xanthine toward the corrosion of 63/67 brass in 2.0 N nitric acid (HNO 3 ) solution. The metal specimens were immersed in the HNO 3 solution for 20 min at 25 • C. Among the three inhibitors, acridine showed the best inhibition efficiency (IE), with an IE of 94% achieved for an inhibitor concentration of 0.004% and a maximum IE of 99.0% obtained for a 0.02% inhibitor concentration.…”
Section: Acridines As Corrosion Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of acridines as corrosion inhibitors dates back to 1975 when Patel and Patel [34] used the weight loss (WL) technique to examine the anticorrosion properties of acridine and analogous phenazine and xanthine toward the corrosion of 63/67 brass in 2.0 N nitric acid (HNO 3 ) solution. The metal specimens were immersed in the HNO 3 solution for 20 min at 25 • C. Among the three inhibitors, acridine showed the best inhibition efficiency (IE), with an IE of 94% achieved for an inhibitor concentration of 0.004% and a maximum IE of 99.0% obtained for a 0.02% inhibitor concentration.…”
Section: Acridines As Corrosion Inhibitorsmentioning
confidence: 99%
“…The use of acridines as corrosion inhibitors dates back to 1975 when Patel and Patel [ 34 ] used the weight loss (WL) technique to examine the anticorrosion properties of acridine and analogous phenazine and xanthine toward the corrosion of 63/67 brass in 2.0 N nitric acid (HNO 3 ) solution. The metal specimens were immersed in the HNO 3 solution for 20 min at 25 °C.…”
Section: Acridines As Corrosion Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various inhibitor platforms are needed to form more effective protective layers for steel protection in hydrochloric acid solution, which makes the exploitation of the late-model chemical class of corrosion inhibitors for mild steel protection a high priority. Acridine derivatives, as a kind of N-heterocyclic organic compound, are easy to be synthesized with perfect inhibition ability and have been under intensive study in metal corrosion inhibition. Granese et al have studied the interactions of acridine inhibitors with Fe and steel surfaces in HCl media and reported that acridine derivatives had good anticorrosion properties. We envisioned that acridine might be such a corrosion inhibitor platform for steel protection as it contains both a polar unit of a nitrogen atom and a large conjugation system.…”
Section: Introductionmentioning
confidence: 99%